Foreign Influence, Nationalism, and the Founding of Modern Chinese Universities - Wenqin, Shen (International Higher Education, 2014)
This article intends to analyze how different foreign models influenced the development of China's higher education system during 1917-1927, and how nationalism became a driving force of this reform. Nowadays, China has to establish a Chinese model of higher education while paying attention to best practices in other countries.